2017
DOI: 10.1103/physrevb.96.184433
|View full text |Cite
|
Sign up to set email alerts
|

Spin-wave propagation in the presence of inhomogeneous Dzyaloshinskii-Moriya interactions

Abstract: We theoretically investigate spin-wave propagation through a magnetic metamaterial with spatially modulated Dzyaloshinskii-Moriya interaction. We establish an effective Schrödinger equation for spin waves and derive boundary conditions for spin waves passing through the boundary between two regions having different Dzyaloshinskii-Moriya interactions. Based on these boundary conditions, we find that the spin wave can be amplified at the boundary and the spin-wave band gap is tunable either by an external magnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…In particular, this numerical technique can be used to calculate the spectrum of spin waves, and when a DMI is present, it reveals different properties characteristic of these systems, such as the spin-wave asymmetry. In this context, simulations have successfully supported theoretical formulations [80,96,97,99,[132][133][134][135][136][137] and experimental measurements [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]138] on thin-film systems with a homogeneous DMI. A micromagnetic simulation is based on numerically discretizing the continuum description of the magnetic system into a mesh of magnetic moments whose arrangement depends on the discretization method.…”
Section: Micromagnetic Simulations Of Spin Waves With Interfacial Dmimentioning
confidence: 64%
“…In particular, this numerical technique can be used to calculate the spectrum of spin waves, and when a DMI is present, it reveals different properties characteristic of these systems, such as the spin-wave asymmetry. In this context, simulations have successfully supported theoretical formulations [80,96,97,99,[132][133][134][135][136][137] and experimental measurements [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]138] on thin-film systems with a homogeneous DMI. A micromagnetic simulation is based on numerically discretizing the continuum description of the magnetic system into a mesh of magnetic moments whose arrangement depends on the discretization method.…”
Section: Micromagnetic Simulations Of Spin Waves With Interfacial Dmimentioning
confidence: 64%
“…The evaluation of the reflection and transmission coefficients requires boundary conditions for spin waves at the heterochiral interface, which are derived below. By defining a spin-wave function Φ = m x + im z and neglecting the damping, we linearize the LLG equation ( 1) and recast it into an effective Schrödinger equation [19]:…”
Section: Analytical Modelmentioning
confidence: 99%
“…The Dzyaloshinskii-Moriya interaction (DMI) [8,9], present in magnetic materials with broken inversion symmetry, has a chiral character and causes the nonreciprocal propagation of spin waves [10][11][12][13], which provides additional functionalities in magnonic devices [14][15][16][17][18]. Recent works found that magnonic crystals with a periodic DMI can efficiently modulate spin-wave propagations and give rise to a plethora of unique effects, such as the spin-wave amplification [19], the emergence of indirect gaps, the formation of flat bands, and an unconventional evolution of the standing spin waves around the gaps [20]. Recently, it has been shown that total reflections and negative refractions can occur at the DMI interface and the spin-wave refraction is not symmetric for positive and negative incident angles [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Section 2.2) [388]. Furthermore, periodical inhomegeneous DMI [407] can result in spin-wave band gaps [405] in a chiral magnonic crystal [408,409,410].…”
Section: Propagating Spin Waves As a Probe Of The Dzyaloshinskii-mori...mentioning
confidence: 99%